Potential perioperative cardiovascular outcomes in cannabis/cannabinoid users. A call for caution - Echeverria-Villalobos, Marco; Guevara, Yosira; Mitchell, Justin; Ryskamp, David; Conner, Joshua; Bush, Margo; Periel, Luis; Uribe, Alberto; Weaver, Tristan E. (Frontiers in Cardiovascular Medicine, 2024)
Background: Cannabis is one of the most widely used psychoactive substances. Its components act through several pathways, producing a myriad of side effects, of which cardiovascular events are the most life-threatening. However, only a limited number of studies address cannabis's perioperative impact on patients during noncardiac surgery. Methods: Studies were identified by searching the PubMed, Medline, EMBASE, and Google Scholar databases using relevant keyword combinations pertinent to the topic. Results: Current evidence shows that cannabis use may cause several cardiovascular events, including abnormalities in cardiac rhythm, myocardial infarction, heart failure, and cerebrovascular events. Additionally, cannabis interacts with anticoagulants and antiplatelet agents, decreasing their efficacy. Finally, the interplay of cannabis with inhalational and intravenous anesthetic agents may lead to adverse perioperative cardiovascular outcomes. Conclusions: The use of cannabis can trigger cardiovascular events that may depend on factors such as the duration of consumption, the route of administration of the drug, and the dose consumed, which places these patients at risk of drugdrug interactions with anesthetic agents. However, large prospective randomized clinical trials are needed to further elucidate gaps in the body of knowledge regarding which patient population has a greater risk of perioperative complications after cannabis consumption.